Comparison of the efficacy and safety of different doses of atropine for myopic control in children: a meta-analysis - Peixian Hou; Peixian Hou; Dawen Wu; Dawen Wu; Yan Nie; Yan Nie; Hong Wei; Hong Wei; Longqian Liu; Longqian Liu; Guoyuan Yang; Guoyuan Yang (Frontiers Media S.A., 2023)
Purpose: To comprehensively reassess the efficacy and safety of different concentrations of atropine for retarding myopia progression and seek the most appropriate therapeutic concentration for clinical practice.Methods: We searched PubMed, Cochrane Library, Embase, Chinese Science and Technology Periodicals (VIP) and China National Knowledege Infrastructure (CNKI) from their inception to 23 March 2023, to obtain eligible randomized controlled trials (RCTs) and cohort studies that had atropine in at least one treatment arm and placebo/no intervention in another arm. We evaluated the risk of bias of the RCTs according to the recommendations of the Cochrane Collaboration for RCTs and quality of cohort studies by the Newcastle‒Ottawa Scale. Weighted mean difference (WMD), 95% confidence interval were calculated for meta-analysis. All data analyses were performed using Review Manager 5.3, STATA 12.0 and SPSS 26.0 software.Results: A total of 44 studies were included in the meta-analysis. Weighted mean difference (WMD) were 0.73 diopters (D), 0.65 D, 0.35 D per year in refraction progression (χ2 = 14.63, I2 = 86.3%; p < 0.001) and −0.26 mm, −0.37 mm, −0.11 mm per year in axial length progression (χ2 = 5.80, I2 = 65.5%; p = 0.06) for high (0.5%-1%), moderate (0.1%-0.25%), and low (0.005%-0.05%) dose atropine groups, respectively. Logarithmic dose‒response correlations were found between atropine and their effect on change of refraction, axial length, accommodation and photopic pupil diameter. Through these curves, we found that atropine with concentrations ≤0.05% atropine resulted in a residual value of accommodation of more than 5 D and an increase in pupil diameter no more than 3 mm. Higher doses of atropine resulted in a higher incidence of adverse effects, of which the incidence of photophobia was dose-dependent (r = 0.477, p = 0.029).Conclusion: Both the efficacy and risk of adverse events for atropine treatment of myopia were mostly dose dependent. Comprehensively considered the myopia control effect and safety of each dose, 0.05% may be the best concentration of atropine to control myopia progression at present, at which myopia is better controlled and the side effects are tolerable.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails, CRD42022377705.